Employee Performance Improvement Through Competence and Organizational Culture with Work Motivation as A Mediation Variable - Nurasniar, Wahyu Apri (Pandawan, 2022)
The performance of employees in government organizations must constantly be improved based on their function as public servants so that government organizations will be able to provide the best service to the needs of the public. This study aimed to examine the effect of competence, organizational culture, and work motivation on improving employee performance. The novelty in this research is that no previous research has been found that discusses improving employee performance through the influence of competence, organizational culture, and work motivation on employees’ section of Bina Marga. The limitation in this study is only to analyze the magnitude of the influence of competence, organizational culture, and work motivation on the employee performance section in Bina Marga. The method used in this study is quantitative. The population and sample of this study were all employees in the Highways Sector as many as 40 people. The data collection technique used a questionnaire with a Likert scale ranging from 1 to 10. Structural Equation Modeling was used to test the statistical significance of the path coefficients. The result of this research is that there is a positive and significant influence between competence on work motivation. Competence has a positive and significant influence on employee performance. Organizational culture has a positive and significant influence on employee performance. Work motivation does not affect employee performance.